Effect of Gu Tong Xian capsule on expression level of type I, II collagen and BMP-2 mRNA in rabbits with fracture during long-distance running - Liang Li; Yueting Qiu (Elsevier, 2017)
The study aims to analyze and investigate the effects of Gu Tong Xian Capsule on the expression level of type I, II collagen and BMP-2 mRNA in rabbits with fracture during long-distance running. 60 adult healthy rabbits were selected as research objects, and then randomly divided into three groups including model group, positive control group and treatment group, each containing 20 rabbits. The three groups were treated with saline gastric lavage, powder for fracture and trauma, and Gu Tong Xian capsule, respectively. The rabbits of the three groups were respectively sacrificed at 1st week, 2nd weeks and 4th week after operation for sample collection. After that, the expression levels of bone collagen type I, II and BMP-2 of three groups were measured and compared with each other. At all stages, the transcriptional level of type I collagen mRNA in the treatment group were significantly higher than that in the positive control group and model group (p < 0.05); Transcriptional level of type II collagen mRNA in the treatment group increased significantly in the first week, then gradually declined in the 2nd and 4th week, with significantly difference to the model group and the positive control group (p < 0.05). In addition, the transcriptional level of bone morphogenetic protein BMP-2 mRNA at fracture site of the treatment group was higher than that of model group and positive control group (p < 0.05). Gu Tong Xian Capsule can significantly promote fracture healing of experiment rabbits and reduce fracture healing time. Moreover, it can well regulate the expression levels of type I, II collagen and transcriptional level ofBMP-2 mRNA in experiment rabbits with fracture. Keywords: Traditional Chinese medicine Gu Tong Xian capsule, Long-distance running, Rabbit with fracture, Type I and II collagen, Expression of BMP-2mRNA, Observation and exploration